Building of a Database for Cyprus Beaches - Monioudi, Isavela N.; Chatzistratis, Dimitris; Chalazas, Theodoros; Savva, Christos S.; Hasiotis, Thomas; Velegrakis, Adonis; Kountouri, Josefina; Mettas, Christodoulos; Evagorou, Evagoras S.; Hadjimitsis, Diofantos G. (My University, 2023)
This contribution presents the first database of beaches (inventory) of Cyprus (Eastern Mediterranean). Satellite images and tools of the Google Earth application, available geospatial information from the 2018 Land Cover/Land Use dataset for Coastal Zones (available by Land Copernicus services) and additional information relying on web resources were used. The subaerial ('dry') beaches were digitized as polygons using a standard operating procedure (SOP) to facilitate consistency, whereas production of metadata from the digitized polygons was carried out in a GIS environment. The database includes geo-spatial characteristics and other attributes of 142 beaches (with an area of 1.23 km2 ) located in the Republic of Cyprus. Archived information on blue flags awards, water quality and environmental protection status (e.g., NATURA 2000) was also collated and stored in the data base. The geographical distribution along the coastline of Cyprus, the spatial characteristics and other attributes of the beaches stored in the database were analysed, using multivariate statistics to identify underlying relationships. The inventory can be easily used for coastal environmental management issues / planning, also related to coastal erosion, a long-term problem for Cyprus beaches that is predicted to exacerbate under the foreseen sea-level rise, enhancing beach squeezing.